The Manifesting Menace of Multidrug Resistant Acinetobacter baumannii - Kulkarni Vishal L; Kinikar A G; Bhalerao D S; Deorukhkar S C; Roushani S B (Microbiology and Biotechnology Research: An Overview Vol. 2, 2025)
Introduction: Infections due to Acinetobacter baumannii have become a global medical challenge. Multidrug-resistant Acinetobacter baumannii (MDRAB) isolates are causing catastrophic consequences in healthcare settings, particularly in critical care areas. Acinetobacter baumannii is one of the six most cardinal pathogens in the ESKAPE group of organisms, which includes Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, A. baumannii, Pseudomonas aeruginosa and Enterobacter species. The mortality in patients who are suffering from A. baumannii infections can be as high as 75%. The most notorious problem encountered is the capacity of these species to acquire the different mechanisms of resistance and the emergence of strains that are resistant to all commonly used antibiotics coupled with the scarcity of development of new antibiotics; this has resulted in a limited choice of antibiotics for treatment of multidrug-resistant Acinetobacter baumannii. Purpose: The purpose of this study was to isolate A. baumannii species from different clinical specimens and to determine their antimicrobial resistance pattern. Methodology: The study was done in the Department of Microbiology, RMC, Loni. The clinical samples were subjected to Gram staining, and aerobic culture using MacConkey and blood agar. Acinetobacter baumannii species were identified by standard microbiological identification methods. Antimicrobial susceptibility testing was done by Kirby Bauer’s disc diffusion technique. Results: A total of 114 Acinetobacter baumannii species were isolated. The maximum number of Acinetobacter baumannii isolates were recovered from pus sample (41.23%) followed by tracheal secretions (30.7%). The rate of isolation of A. baumannii was highest in critical care areas (42.11%). The highest resistance was noted against Tobramycin (100%) followed by Cefotaxim (98.4%), Piperacillin (96.8%), and Ceftazidime (96.2%). All strains were sensitive to Polymyxin B & Colistin. Multidrug-resistant A. baumannii isolates were found to be 77.19%. Conclusion: This study demonstrates the alarming nature of multidrug-resistant organisms in critical care areas. Stringent vigilance and regular surveillance in critical areas to prevent colonization as well as cross-infection is recommended. In addition to that, effective infection control protocols, regular practice of hand hygiene and strict implementation of antibiotics policy may help to control multidrug-resistant Intensive care unit (ICU) bugs.